Electrostatic interaction induced nucleation and growth of self-assembled nanostructures. Issue 1 (January 2015) - Sahoo, Trilochan; Jang, Lee-Woon; Yu, Yeon-Tae; Lee, In-Hwan
Abstract: We performed in-situ growth of self-assembled nanostructures (SANs) by a wet chemical technique, and demonstrated that electrostatic interactions could be exploited for the initiation of nucleation and growth of SANs at a solid–liquid interface. The formation of SANs of cobalt compound on a Si substrate together with their morphology and structure were investigated. The creation of nucleation sites was attributed to electrostatic adsorption, and in principle a specific adsorption approach could also be invoked for the preparation of SANs. It was found that the SANs of different sizes and shapes could be obtained by varying the concentration of cobalt solution and reducing agent.